DENSITY AND VELOCITY MEASUREMENTS IN TURBULENT HE-AIR BOUNDARY LAYERS (Sciences & Technology. A, exactes sciences, 2003)
A turbulent  boundary layer with large density variations has been generated by tangential injection of air or helium Into a boundary layer of air-helium mixture. Instrumentation based on thermo- anemometry has been successfully developed for the investigation of this flow  Analysis or the mean and fluctuating density fields shows that the flow is mainly governed by the ratio of the injection to the external velocity and that the density ratio plays a secondary role in the mixing processes. However, a sight enhancement of turbulent activity is observed when helium is injected.